Adherence to oral therapies among patients with renal cell carcinoma: Post hoc analysis of the ECOG‐ACRIN E2805 trial. (18th August 2021) - Murphy, Caitlin C.; Fullington, Hannah M.; Gerber, David E.; Bowman, Isaac Alex; Puligandla, Maneka; Dutcher, Janice P.; DiPaola, Robert S.; Haas, Naomi B.
Abstract: Background: As use of oral cancer therapies increases, patient adherence has become critical when evaluating the effectiveness of therapy. In a phase III trial for renal cell carcinoma, we: (a) characterized adherence to sorafenib, sunitinib, and/or placebo and (b) identified factors associated with non‐adherence. Methods: ECOG‐ACRIN E2805 was a double‐blind, placebo‐controlled, randomized trial comparing adjuvant sorafenib or sunitinib in patients with resected primary renal cell carcinoma at high risk for recurrence. We used patient‐completed pill diaries to measure adherence as the number of pills taken divided by the number of pills prescribed. Log‐binomial regression was used to identify correlates of non‐adherence (<80% of prescribed pills reported as taken). Results: Mean adherence was 90.7% among those assigned to sunitinib (n = 613) and 84.8% among those assigned to sorafenib (n = 616). Among those assigned to placebo, mean adherence was 94.9% and 92.4% to sunitinib and sorafenib placebo, respectively. Non‐adherence was associated with race/ethnicity (non‐Hispanic Black: prevalence ratio [PR] 2.22, 95% CI 1.63, 3.01; Hispanic: PR 1.54, 95% CI 1.05, 2.26), high volume enrollment (≥10 patients: PR 1.30, 95% CI 1.03, 1.64), treatment group (sunitinib: PR 2.24, 95% CI 1.66, 3.02; sorafenib: PR 2.37, 95% CI 1.74, 3.22), and skin rash (PR 1.36, 95% CI 1.03, 1.80). Conclusion: Among patients participating in a randomized clinical trial, adherence to oral cancer therapies was lower compared to placebo. Adherence was also worse in racial/ethnic minorities, those experiencing toxicities, and high volume enrolling sites. Our findings highlight several challenges to address in clinical practice as use of oral therapies continues to increase. Clinical trial registration number: This trial is registered with ClinicalTrials.gov, number NCT00326898. Abstract : In a randomized clinical trial for renal cell carcinoma, adherence to oral therapy was lower (85%) than adherence to placebo (95%). Adherence was also worse among racial/ethnic minorities, patients experiencing certain toxicities, and high volume enrolling sites, highlighting several challenges to address in clinical practice as oral therapies become increasingly common.